PENGARUH PENGGUNAAN MEDIA PHET TERHADAP MOTIVASI BELAJAR DAN KEMAMPUAN PEMECAHAN MASALAH SISWA PADA MATERI RANGKAIAN LISTRIK SISWA KELAS X KOMPETENSI KEAHLIAN TITL SMK NEGERI 7 SURABAYA - Ahmad Dion Eka Saputra; Puput Wanarti Rusimamto; Joko Joko; Tri Rijanto (Jurnal Pendidikan Teknik Elektro, 2027)
This study investigates the effectiveness of PhET simulation in improving learning motivation and problem-solving skills in the context of electrical circuit materials in the Electrical Power Installation Engineering (TITL) expertise program at SMK Negeri 7 Surabaya. In this study, a quantitative paradigm is adopted and uses a one-class pre-experimental research design. Data collection was carried out using two assessment instruments. Students' motivation towards learning was measured through questionnaires based on self-determination theory (SDT). Meanwhile, problem-solving competencies are evaluated through tests developed according to Polya's four-stage problem-solving model. Before performing hypothesis testing, the normality of the data is checked to determine the suitability of statistical procedures. Then the T test of paired samples was applied to analyze changes in learning motivation, while differences in problem-solving performance were assessed using the wilcoxon test through SPSS. The implementation of the PhET simulation after being analyzed had a significant effect on the increase in student learning motivation, this was shown by the results of the paired sample t-test resulting in a value of 0.000 which was smaller than the standard significance of 0.05. Similar findings were also obtained for problem-solving competencies. The results of the wilcoxon test obtained a value of 0.000 which is also smaller than the standard value of 0.05. This confirms that there are significant differences before and after the intervention to students. These findings suggest that learning with the help of PhET simulation media is effective in increasing students' learning motivation and problem-solving competencies